Distribution Grid Reactive Power Optimization Based on Improved Cloud Particle Swarm Algorithm - Hongsheng Su (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
To resolve the problems that cloud particle swarm optimization(CPSO) was easily trapped in local minimum and possessed slow convergence speed and early-maturing during distribution grid reactive power optimization, CPSO algorithm was improved based on cloud digital features in this paper. The method firstly combined Local search with global search together based on solution space transform, where the crossover and mutation operation of the particles were implemented based on normal cloud operator. And then the dramatic achievements were acquired in time-consuming and storage-cost using the improved algorithm. Finally, applied in bus IEEE30 system, the simulation results show that the better global solution is attained using the improved CPSO algorithm, and its convergence speed and accuracy possesses a dramatic improvement. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1727